Environmental and socioeconomic determinants of child mortality: Evidence from the 2013 Nigerian demographic health survey (2016)
Despite the global decline in under-five mortality rate from 91 deaths per 1000 live births in 1990 to 43 deaths per 1000 live births in 2015 and Nigeria’s under-five mortality reduction from 201 per 1,000 live births in 2009 to 128 per 1,000 live births in 2013 as against the Sustainable Development Goal target of 25 per 1,000 live births, child mortality rate still remain unacceptably high in Nigeria and thereby has a long way to go in achieving this target. This study explores the household’s environmental, socio-economic characteristics, maternal demographic and their effect on child mortality. Data from the Nigeria Demographic and Health Survey (NDHS) 2013 was used to investigate the predictors of child (aged 0-4 years) mortality in Nigeria. Data for the currently married women who had experienced child mortality and those who have not, totaling 20,192. Cross-tabulation and binary logistic regression techniques were employed in the statistical analysis. The result indicated that child mortality rate was highest (46.0%) among mothers with no educational and lowest (13.6%) among mothers with tertiary education and was statistically significant in reducing the child mortality rate. Children born in households with unimproved toilet experienced highest mortality rate (41.0%) compared to those who were born in households with improved toilet (30.4%) and have substantial impact on child mortality. Maternal education and provision of sanitation facilities should be advocated as a strategy to reduce child mortality.